SYNERGISTIC COMBINATION OF Curcuma xanthorrhiza, Ficus septica AND DOXORUBICIN INHIBITS METASTASIS OF BREAST CANCER THROUGH INHIBITION MMP-9 ACTIVITY - Ika Rahmawati Sutejo; Herwandhani Putri; Edy Meiyanto (UPT Penerbitan Universitas Jember)
Breast cancer is one of the most commonmalignancy on woman in Indonesia (Kemenkes RI,2015). Breast cancer patients usually come todoctor in a late stage & the deaths are due to thecomplications of metastasis in vital organs (NationalCancer Institute, 2012). The death case mostprobably happened when cancer is aggresive &distant metastazed. One factor that causingaggresivity & metastasis is presence of HER2 protein.HER2 is found in 25% cases of Ca mammae. Her2status also influences preference of drug for cancertreatment. Besides of antibodi monoklonal &antireseptor of tirosine kinase, doxorubicin is stillused for treatment breast cancer with overexpressHER2 (Nielsen et al., 2009). Long term use ofdoxorubicin causes several side effects, resistanceand toxicity to normal tissues (Smith et al., 2010).Therefore, combining doxorubicin withchemopreventive agent is needed to increaseactivity of doxorubicin, to overcome the drugresistance and to reduce its side effect (Sarkar andLi, 2006). Chemopreventive agent used in thisresearch are temulawak (Curcuma xanthorrhiza) andawar-awar (Ficus septica). The leaves of Ficus septicahave been used to treat colds, fungal and bacterialdiseases, and various cancers. The ethanolic extractof Ficus septica showed a cytotoxic effect on breastcancer T47D cell lines with IC50 value of 13 μg/mL.The extract at 4.88 μg/mL also showed an optimumsynergistic effect in combination with doxorubicin(3.75 nmol) (Pratama et al., 2010). In addition, theextract induced apoptosis and down regulated theexpression of Bcl-2 protein in breast cancer cellsMCF-7 (Sekti et al., 2010). The major components ofC. xanthorrhiza are curcumin and xanthorrhizol.Curcumin suppresses a number of key elements incellular signal transduction pathways pertinent togrowth, differentiation, and malignanttransformation (Kunumakkara et al., 2008). Choi etal. (2005) observed that injection of 0.2-1.0 mg/kgbw xanthorrhizol had an antimetastatic effect in amouse lung metastasis model.It is a general assumption that combinationtreatment is sometimes more beneficial than singlecompounds. The previous study reported thatcombination of doxorubicin and chemopreventiveagent showed synergistic effect in cancer treatment(Lewandowska et al., 2014). The purpose of thisstudy is to prove antimetastasis effect ofcombination of ethanolic extract of rhizome ofCurcuma xanthorrhiza (ECx), ethanolic extract ofleave of Ficus septica (EFs), and doxorubicin solelyand its combination on MCF7-HER2 breast cancercell line through inhibition activity of MMP-9.Cytotoxic assay is used to determine the synergy ofcombinations. Antimetastasis effect was observedthrough inhibition of cancer cell invasion. Gelatinzymography signify the inhibitory activity of MMP-9,which plays an important role in cancer cell invasion.